Research on the properties of sorbents and decontaminants in the processes with small isotope effects - Levenets, V.V.; Lonin, A.Yu.; Omelnik, O.P.; Shchur, A.O. (Вопросы атомной науки и техники, 2021)
The low values of isotope effects in the sorption/decontamination processes make it possible to investigate the properties of the sorbing and decontaminating agents with the use of stable isotope simulators. In the work presented here the element content was determined from the characteristic X-ray emission induced by the proton beam (PIXE), by gamma-ray emission from the radioactive source, and by emission from the X-ray tube. Based on the results of efficiency determination for different kinds of sorbents and decontaminants, recommendations have been given for the choice of materials having the wanted performance characteristics. Завдяки малим значенням величин ізотопних ефектів у процесах сорбції та дезактивації можливо вивчення властивостей досліджуваних нами сорбентів і дезактивуючих засобів з використання імітаторів зі стабільними ізотопами. У представлених дослідженнях елементний вміст визначався з використанням характеристичного рентгенівського випромінювання, що порушувався пучком протонів, гамма-випромінюванням від радіоактивного джерела, випромінюванням від рентгенівської трубки. За результатами визначення ефективності різних типів сорбентів і дезактивуючих засобів надано рекомендації щодо вибору матеріалів з необхідними характеристиками. Благодаря малым значениям величин изотопных эффектов у процессах сорбции и дезактивации возможно изучение свойств исследуемых нами сорбентов и дезактивирующих средств по использованию имитаторов со стабильными изотопами. В представленных исследованиях элементное содержание определялось с использованием характеристического рентгеновского излучения, возбуждаемого пучком протонов, гаммаизлучением от радиоактивного источника, излучением от рентгеновской трубки. По результатам определения эффективности различных типов сорбентов и дезактивирующих средств даны рекомендации по выбору материалов с необходимыми характеристиками.